Towards a Poetics of Affect: Staging Sound in Wajdi Mouawad's Theatre of Compassion - Meerzon, Yana (Recherches sémiotiques / Semiotic Inquiry, 2016)
Erin Hurley and Sara Warner in their insightful study “Affect/Performance/Politics” (2012) remind us that the humanities and social sciences today experience a new sweep of theoretical inquiry, focusing on studying affect or thrill experience as a leading mechanism of our cognition and communication, as well as the making and reception of art works. Today, “the affective turn signals [our] renewed interest in embodiment and sensorial experience” (2012 : 99), allowing scholars to examine a theatrical performance as a venue to reinforce the subjectivity of the artist and that of the receiver. A theory of affect strives to describe the mechanisms of reception in theatre as our psycho-physical experience, regardless of our linguistic, cultural, social, or ethnic background, and thus aspires to bring the question of universals back to the rehearsal hall and the theatre auditorium. This article takes such a theoretical framework further to argue that in today’s theatre it is the multiple soundscapes of performance – actors’ voices, music, artificially produced and live sound, the architecture of performance aurality – that has the most potential for instigating the audiences’ visceral experience. Hans Thies Lehmann (2006) in his influential book on post-dramatic theatre aesthetics names this phenomenon as chora, the sonoric space of the performance, which possesses the great power to deconstruct the semantic meanings of words, turning them into mechanisms of performative psycho-physical affect as xperienced by the audience (ibid. : 145). In order to illustrate how words (as poetry) and sounds (as singing and music) generate affect in today’s performances, an example of Lehmann’s chora-graphy (2006 : 146), I examine Wajdi Mouawad’s theatre of compassion (Naugrette 2008 : 88), emphasizing his dramaturgy, directorial choices (mise-en-scene), use of sound, and work with actors, as an artistic project called to shock and shake audiences emotionally. In the first section of my study I outline the major principles of the theory of affect; in the second, I discuss Mouawad’s approach to staging a canonical dramatic text and investigate how sound serves as the leading compositional element of affect in his 2011 production Des Femmes, an adaptation of Sophocles’ three tragedies Les Trachiniennes, Antigone and Électre.